PERAN TABAYYUN FAJAR DALAM MEMINIMALKAN KESALAHAN PENETAPAN AWAL WAKTU SALAT SUBUH DI KELURAHAN PARANG TAMBUNG KOTA MAKASSAR - Rahmadani, Eka Suci; Chotban, Sippah (HISABUNA: Jurnal Ilmu Falak, 2025)
Abstract The main issue addressed in this study is how to identify the causes of errors in the initial determination of the Fajr (Subuh) prayer time and the role of tabayyun (verification) in minimizing such errors in Parang Tambung Subdistrict, Makassar City. The research method used is field research employing a descriptive qualitative model. The research approaches applied include the shar‘i (Islamic legal), astronomical, and phenomenological approaches. Data were collected through observation, interviews, and documentation from local religious figures and mosque administrators, as well as secondary sources such as relevant literature and documents. The data were then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The research findings indicate that errors in determining the Fajr prayer time are caused by differences in calculation methods, particularly regarding the sun's depression angle, the lack of direct observation of the true dawn (fajr shadiq), and complete reliance on prayer time calendars without field verification. Tabayyun of the dawn plays a crucial role in correcting this issue through direct observation of the appearance of fajr shadiq. These findings suggest that the actual fajr shadiq observed in the field does not always align with the -20° standard used in calculation-based calendars. Therefore, the verification process through tabayyun is essential to ensure the accuracy of Fajr prayer time in accordance with Islamic teachings. The implication of this study is the importance of applying the principle of tabayyun as both a preventive and corrective measure in determining prayer times and as a reference for religious institutions in evaluating the current standards of Fajr prayer timing. Keywords: ajr Verification, Subuh Prayer Time, Fajr Shadiq,Hisab, Rukyat